Dietary Chia (Salvia hispanica L.) seeds oil supplementation augments growth performance and gut microbial composition in Labeo rohita fingerlings - Sanjay Kumar Gupta; Akruti Gupta; Jaipal Singh Choudhary; Md Javed Foysal; Rajan Gupta; Biplab Sarkar; K. K. Krishnani (Scientific Reports)
Abstract The present study investigates the supplemental effects of chia seed oil (CSO) on the growth performance and modulation of intestinal microbiota in Labeo rohita fingerlings. Four diets were formulated with graded levels of CSO: 1.0%, 2.0%, and 3.0% represented as CSO (1), CSO (2), and, CSO (3) groups alongside a control group without CSO. L. rohita fingerlings (n = 180) (mean weight = 19.74 ± 0.33 g) were randomly distributed in triplicates for 60 days to these treatment groups. The results depicted significant improvements (p < 0.05) in weight gain (WG) %, specific growth rate (SGR), feed conversion ratio (FCR), and feed conversion efficiency (FCE) in the group supplemented with the lowest level of CSO. Gut microbial analysis evidenced the ability of CSO at 1.0% to augment the relative abundance of bacterial phyla such as Verrucomicrobiota, Actinobacteria, Bacteroidota, Fusobacteria and Firmicutes, as well as genera Luteolibacter and Cetobacterium, indicating higher alpha diversity compared to the control. Principle coordinate analysis (PCoA) demonstrated a distinct composition of microbial communities in CSO-supplemented groups relative to the control (p < 0.001). Correlation analysis further revealed a significant (p < 0.05) association of specific microbial taxa with growth performance parameters. The predictions of metabolic pathways suggested the involvement of carbohydrate and amino acid metabolic pathways in the CSO (1) group, indicating improved nutrient transport and metabolism. Overall, the findings highlight the beneficial effects of 1.0% CSO supplementation on growth performance and modulation of gut microbiota in L. rohita fingerlings.